Does public investment contribute to increasing institutional and interpersonal trust? Place-based policies for sports and cultural activities in Cali, Colombia - Lina María Martínez; Juan Tomás Sayago (Inter-American Development Bank (IDB), 2021)
This paper studies the effect of two place-based policies implemented in Cali, Colombia on social capital and trust. We use the CaliBRANDO survey to account for institutional and interpersonal trust, matching neighborhood of residence and where policies are applied. We set up a difference-in-difference model to estimate the impact of the policies on the indexes that measure trust. We nd that the organized sport policy improves institutional trust by about 4%. Our results are significant for soccer and basketball and not significant for futsal and other activities. The evidence does not support an effect of nightlights on trust.
Keywords: H41; O20; R1; C21; L38; 330; Trust; Place-based policies; Impact evaluation; Social capital; Urban policy